Comparative Advantage in Indian Economy: 1990-2014 - Fathipour, Gholamreza; Gaikwad, Pratibha S. (Information Management and Business Review, 2018)
The most countries try to improve their advantage towards goods with high range of demand and sustainable trade such as industrial goods and merchandise. India embarked on the path of globalization in the early 1990s with the objective to attain a higher growth profile. This question can be brought up in which goods India has have comparative adventage. The aim of this study is to analyze comparative advantages of Indian’s exports commodities during of post liberalsation in 1990-2014. The well-known index for determining trade advantage is revealed comparative advantage (RCA) by Balasa. The findings by Indiaâ€™s RCA in exports showed India has gained comparative advantage in a number of agriculture sector such as Food items, Textiles, Leather and other Manufactures.